Spatial and Temporal Patterns in Arctic Fox Diets at a Large Goose Colony - Bantle, Jason L.; Alisauskas, Ray T. (ARCTIC, 1998)
We studied diets of arctic foxes (Alopex lagopus) associated with a large nesting colony of lesser snow and Ross's geese in the central Canadian Arctic. From 15 May to 5 August 1994 and from 18 May to 7 August 1995, we examined arctic fox diets using frequency of occurrence of prey remains in faeces. Most scats (n=791 of 817, or 97%) were collected from den sites. Scats from foxes with dens inside the goose colony contained eggs more frequently than those of foxes that depended more on small mammals outside the colony. Foxes were opportunistic in their feeding habits, as prey use was linked to the nesting cycle of geese, coinciding to periods of egg, goose, and gosling abundance. However, diets in spring, i.e., before geese arrive, reflected the importance to arctic foxes of caching geese and eggs from the previous summer at Karrak Lake. We suggest that large increases in nesting populations of lesser snow and Ross's geese may have beneficial implications for arctic fox populations over a large area. On a étudié le régime alimentaire du renard arctique (Alopex lagopus) associé à une vaste colonie nicheuse de petites oies blanches et d'oies de Ross dans le centre de l'Arctique canadien. Du 15 mai au 5 août 1994, et du 18 mai au 7 août 1995, on a examiné le régime alimentaire du renard arctique en utilisant la fréquence de l'occurrence de restes de proies dans les crottes. La plupart (n = 792 sur 817, ou 97 p. cent) ont été recueillies sur les sites des terriers. Les crottes des renards dont le terrier se trouvait à l'intérieur de la colonie d'oies contenaient plus souvent des oeufs que celles des renards dont le terrier était situé en dehors de la colonie et qui dépendaient plus des petits mammifères. Les renards se montraient opportunistes dans leurs habitudes alimentaires, l'utilisation des proies étant liée au cycle nicheur des oies et coïncidant avec des périodes d'abondance d'oeufs, d'oies et d'oisons. Toutefois, les régimes alimentaires au printemps, c'est-à-dire avant l'arrivée des oies, reflétaient ...